Tungsten Chemical Mechanical Polishing Slurry

JP2024544194A5Pending Publication Date: 2024-12-13VERSUM MATERIALS US LLC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024532741
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-12-02
Filing Date
2022-11-29
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

Existing chemical mechanical polishing (CMP) slurries for tungsten in semiconductor manufacturing face challenges in minimizing dishing and erosion while maintaining desired removal rates, which are crucial for achieving functional semiconductor devices.

Method used

The development of CMP slurries comprising specific formulations including silica abrasive particles surface-treated with alkoxysilane amine compounds, oxidizing agents, and additives like chitosan and polyacrylamide, which provide enhanced selectivity and control over tungsten polishing rates, reducing dishing and erosion.

Benefits of technology

The new CMP slurries achieve improved tungsten removal rates with reduced dishing and erosion, maintaining planarity and integrity of semiconductor features, thereby enhancing the performance and reliability of semiconductor devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

The present invention relates to a slurry, method and system that can be used in chemical mechanical planarization (CMP) of tungsten-containing semiconductor devices. A CMP slurry containing silica particles, optionally treated with an alkoxysilane amine compound, an oxidizer, at least one nitrogen-containing polymer additive, and an activator for tungsten polishing shows improved tungsten removal rate and tungsten to TEOS removal selectivity without affecting dishing and erosion topography.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This patent application claims the benefit of U.S. Provisional Patent Application No. 63 / 264,801, filed December 2, 2021, which is incorporated by reference herein in its entirety. [Background technology]

[0002] The present invention relates to slurries, systems and methods used for chemical mechanical polishing or planarization (CMP) of semiconductor devices, particularly for tungsten-containing materials.

[0003] Integrated circuits are interconnected through the use of well-known multi-layer wiring. The interconnect structure usually has a first layer of metallization, an interconnect layer, a second level of metallization, and typically a third and subsequent levels of metallization. Interlayer dielectric materials such as silicon dioxide and sometimes low-k materials are used to electrically isolate different levels of metallization within a silicon substrate or well. Electrical connections between different interconnect levels are made through the use of metallized vias, and in particular tungsten vias. U.S. Pat. No. 4,789,648 describes a method for preparing multiple metallized layers and metallized vias in an insulator film. In a similar manner, metal contacts are used to make electrical connections between devices formed within the interconnect levels and wells. Metal vias and contacts are typically filled with tungsten, and typically employ an adhesion layer, such as titanium nitride (TiN) and / or titanium, to adhere the metal layer, such as the tungsten metal layer, to the dielectric material.

[0004] In some semiconductor manufacturing processes, metallized vias or contacts are formed by blanket tungsten deposition followed by a CMP step. In a typical process, a via hole is etched through an inter-level dielectric (ILD) into an interconnect wiring or semiconductor substrate. A thin adhesion layer, such as titanium nitride and / or titanium, is then typically formed on top of the ILD and directed into the etched via hole. A tungsten film is then blanket deposited over the adhesion layer and into the via. Deposition is continued until the via hole is filled with tungsten. Finally, the excess tungsten is removed by CMP to form the metal via.

[0005] In another semiconductor manufacturing process, tungsten is used as the gate electrode material in transistors because it has better electrical properties than polysilicon, which has traditionally been used as the gate electrode material, as taught by A. Yagishita et al., IEEE TRANSACTIONS ON ELECTRON DEVICES, VOL. 47, NO. 5, MAY 2000.

[0006] In a typical CMP process, the substrate is placed in direct contact with a rotating polishing pad. The carrier applies pressure against the backside of the substrate. During the polishing process, the pad and table rotate while a downward force is maintained against the backside of the substrate. During polishing, an abrasive, chemically reactive solution, commonly referred to as an abrasive "slurry", abrasive "composition" or abrasive "formulation", is deposited on the pad, and the rotation and / or motion of the pad relative to the wafer brings the slurry into the space between the polishing pad and the substrate surface. The slurry initiates the polishing process by chemically reacting with the film being polished. The polishing process is driven by the rotational motion of the pad relative to the substrate as the slurry is presented to the wafer / pad interface. Polishing continues in this manner until the desired film on the insulator is removed. It is believed that the removal of tungsten in CMP is due to a synergistic effect between mechanical wear and the oxidation and subsequent dissolution of tungsten.

[0007] One of the problems commonly encountered in CMP, especially in metal applications such as tungsten, is dishing of the tungsten lines and erosion of arrays of metal lines. Tungsten CMP slurries must be formulated to minimize dishing and erosion in order to meet specific design goals that are important for functional devices.

[0008] There remains a need for new CMP tungsten slurries that can reduce erosion while maintaining a desired removal rate during polishing. Summary of the Invention

[0009] The present invention relates to CMP slurries, systems and methods of using CMP slurries that reduce dishing while maintaining a desired removal rate in polishing semiconductor devices or substrates, and more particularly, to CMP slurries, systems and methods of using CMP slurries that provide highly selective tungsten slurries with excellent dishing and erosion performance during polishing of tungsten-containing semiconductor devices or substrates.

[0010] In one aspect, the present disclosure provides a polishing composition comprising: water; abrasive particles comprising 0.05% to 10.0% by weight silica; 0.005% to 0.5% by weight of a soluble activator compound; 0.5% to about 10.0% by weight of an oxidizer; at least one nitrogen-containing polymeric additive selected from the group consisting of chitosan, polyacrylamide, polyamine, polyethyleneimine, poly(N-vinyl-N-methylamine), polyaminostyrene, polyvinylamine, (polyvinyl)amine; and, optionally, a corrosion inhibitor; a stabilizer; a pH adjuster; a water-miscible organic solvent; a surfactant; and a biocide or biological growth inhibitor, wherein the polishing composition has a pH of 1 to 7.

[0011] In another aspect, provided herein is a polishing composition comprising water; abrasive particles comprising 0.05% to 10.0% by weight silica; 0.005% to 0.5% by weight of a soluble activator compound; 0.5% to about 10.0% by weight of an oxidizing agent; and at least one water soluble cationic polysaccharide, the water soluble cationic polysaccharide being at least one represented by the general formula: [ka] R sacch is a residue of a polysaccharide repeat unit derived from a polysaccharide source; Q is selected from the group consisting of: [ka] R4 is [ka] and, [ka] and hydrogen; Z is 50 to about 20,000; each R1, R2, and R3 is independently represented by the following substituent structural formula: [ka] A is an anion; a is an integer from 1 to about 3; m is an integer from 0 to about 6; n is an integer from 0 to about 3, with the proviso that the level of cationic substitution, CS, defined by the average number of moles of quaternary nitrogen atoms per mole of polysaccharide repeat unit, is greater than 0; p is an integer from 0 to about 6; q is 0 or 1; each of R5 and R7 is independently ethylene, propylene, or hydroxypropylene; R6 is a divalent or trivalent, branched or straight chain, saturated or unsaturated hydrocarbon having 2 to about 4 carbon atoms, with the proviso that there are at least 2 carbon atoms between the nitrogen atom and any oxygen atom; R8 is hydrogen, hydroxyl, R h , carboxyl or alkali metal or amine carboxylate, provided that when q is 0, R8 is hydrogen or R h and each R9, R10 and R 11 is individually Rh, alkyl, aryl, aralkyl, alkaryl, cycloalkyl, alkoxyaryl, or alkoxyalkyl having at least two carbon atoms separating the oxygen atom in the alkoxyaryl or alkoxyalkyl group from the nitrogen atom; R h is a hydrophobic group containing an alkyl group having at least 8 carbon atoms; v is equal to the valence of A; y is 0 or 1, and the polishing composition has a pH of 1-7.

[0012] In another aspect, provided herein is a polishing method for chemical mechanical planarization of a semiconductor device comprising at least one surface containing tungsten, comprising the steps of contacting at least one tungsten-containing surface with a polishing pad; water; abrasive particles comprising 0.05% to 10.0% by weight silica; 0.005% to 0.5% by weight of a soluble activator compound; 0.5% to about 10.0% by weight of an oxidizing agent; chitosan, polyacrylamide, polyamine, polyethyleneimine, poly(N-vinyl-N-methylamine), polyaminostyrene, polyvinylamine, (polyvinyl)amine, polyvinyl ... and optionally a corrosion inhibitor; a stabilizer; a pH adjuster; a water-miscible organic solvent; a surfactant; and a biocide or biological growth inhibitor. The polishing composition has a pH of 1 to 7 to at least one surface containing tungsten; and c) polishing the at least one surface containing tungsten with the polishing composition; wherein the polishing rate of tungsten at 3 psi down force is greater than 4000 Å / min. [Brief description of the drawings]

[0013] The present invention is described below in conjunction with the accompanying drawings, in which like numerals refer to like elements, and in which:

[0014] [Figure 1]FIG. 1 shows the removal rates for tungsten (W) and TEOS, and the removal selectivity of W:TEOS using different formulations. [Diagram 2] FIG. 2 shows the measured dishing on tungsten patterned wafers using different formulations. [Diagram 3] FIG. 3 shows the measured erosion on tungsten patterned wafers using different formulations. [Figure 4] FIG. 4 is a graph showing the erosion inhibition effect of chitosan at various concentrations for 1μ features. [Diagram 5] FIG. 5 is a graph showing the erosion inhibition effect of chitosan at various concentrations for 0.25μ features. [Figure 6] FIG. 6 is a graph showing the erosion inhibition effect of chitosan at various concentrations for 0.18μ features. [Figure 7] FIG. 7 is a graph showing the dishing suppression effectiveness of various compositions disclosed herein for 10μ features. [Figure 8] FIG. 8 is a graph showing the dishing suppression effectiveness of various compositions disclosed herein for 1μ features. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] The formation of conductive metal features in semiconductor device wafer manufacturing processes involves patterning the wafer, etching wiring trenches or vias in a dielectric material, filling these vias or wiring trenches with a conductive metal, and then performing chemical mechanical planarization (CMP) to remove excess metal and provide a highly planar surface. The key CMP parameters that define the planarity of a polished wafer are dishing and erosion. Dishing refers to the depression of individual wiring or vias relative to the field level. Dishing is primarily a significant issue for larger features (typically larger than 1 micron) and areas with low patterning density. Erosion is the depression of an array of metal structures compared to the field level. Erosion is generally more problematic for dense arrays of narrow metallization structures with feature sizes of 10 microns or less and patterned metal densities of 50% or more.

[0016] A depiction of the dishing and erosion topography observed after CMP is shown in FIG. 1 of Elbel et al., J. Electrochem Soc., Col. 145, No. 5, May 1998, pp. 1659-1664.

[0017] The present invention relates to slurries that can be used in chemical mechanical planarization (CMP) of tungsten-containing semiconductor devices, substrates, or films. The CMP slurries of the present invention provide unique results of reduced dishing of tungsten structures and reduced erosion of dielectric materials while providing high removal rates.

[0018] The tungsten film may be pure tungsten or may contain alloying elements.

[0019] The formulation of the present invention can be suitable for many kinds of dielectrics used in patterning structure.The examples of dielectric materials include but are not limited to thermal oxide, tetraethyl orthosilicate (TEOS), high density plasma (HDP) oxide, high aspect ratio process (HARP) film, fluorinated oxide film, doped oxide film, organosilicate glass (OSG) low-k dielectric film, spin-on glass (SOG), polymer film, flowable chemical vapor deposition (CVD), silicon nitride, silicon carbide, silicon oxycarbide, silicon oxynitride, silicon oxycarbonitride.

[0020] In some other embodiments, the desired polishing selectivity between tungsten and TEOS removal rates is greater than 25, or preferably greater than 40, or more preferably greater than 90.

[0021] The CMP slurry contains silica particles surface-treated with an alkoxysilane amine compound, an oxidizing agent, an activator for tungsten polishing, and an aqueous solvent, and the pH of the slurry is 2 to 14, preferably 1 to 7, and more preferably 2 to 5.

[0022] The alkoxysilane amine treated silica particles do not contain an alkoxysilane modified shell structure.

[0023] The size of the particles, as measured by dynamic light scattering, is 10 nm to 300 nm, preferably 20 nm to 200 nm, or more preferably 30 to 100 nm; the zeta potential on the particles is 15 mV or more, preferably 20 mV or more, or more preferably 25 mV or more.

[0024] The CMP slurry may optionally include surfactants; stabilizing and passivating agents; dispersants; chelating agents; film-forming anti-corrosion agents; dishing reduction agents, and polishing enhancers.

[0025] In certain preferred embodiments, the polishing rate of a tungsten blanket film at a down force of 3.0 psi and a table speed of 80 RPM is greater than 2500 Å / min, preferably greater than 3000 Å / min, more preferably greater than 4000 Å / min, or most preferably greater than 4500 Å / min; while the polishing rate of TEOS is less than 150 Å / min, preferably less than 80 Å / min, or more preferably less than 50 Å / min.

[0026] In certain preferred embodiments, the erosion of a 9×1 micron array (9 micron wide tungsten lines separated by 1 micron wide dielectric lines) measured on a patterned wafer is less than 1000 Å, preferably less than 500 Å, or more preferably less than 300 Å when the wafer is polished for an additional 15 seconds after the patterned wafer polishing endpoint detected by using a suitable method such as eddy current measurement or optical endpoint detection.

[0027] Abrasives The CMP slurry compositions disclosed herein include 0.01 wt.% to 10.0 wt.%; 0.01 wt.% to 2.0 wt.%; 0.01 wt.% to 0.5 wt.% of abrasive particles, optionally including surface-modified silica particles having surfaces treated with an alkoxysilane amine compound.

[0028] The abrasive is generally in the form of abrasive particles, typically many abrasive particles, of one material or a combination of different materials.

[0029] Generally, suitable abrasive particles are roughly spherical or cocoon-shaped and have an effective diameter of 10 to 300 nm, preferably 20 to 200 nm, or more preferably 30 to 100 nm.

[0030] The abrasive in the form of aggregated or agglomerated particles is preferably further processed to form individual abrasive particles.

[0031] Particle size may be measured by any suitable technique, including, but not limited to, static light scattering, dynamic light scattering, hydrodynamic fluid fractionation, sedimentation analysis, electrical sensing zone analysis and dynamic image analysis, disc centrifuge analysis. A preferred method for particle size and size distribution measurement is dynamic light scattering.

[0032] In some embodiments, the abrasive particles do not have their surfaces modified, hi other embodiments, the abrasive particles are silica particles that have their surfaces treated with an alkoxysilane amine compound.

[0033] The silica particles may be produced by any suitable technique, including, but not limited to, sol-gel, hydrothermal, hydrolytic, plasma, pyrogenic, aerogel, fume and precipitation techniques, and any combination thereof.

[0034] In a preferred embodiment, the alkoxysilane amine compound used to treat the silica particle surface also contains an amino group.

[0035] Alkoxysilane amine compounds can be represented by the following general structure: [ka] R1, R2, R3, and R4 are independently selected from alkyl or aryl groups, or hydrolyzable groups such as alkoxy, acyloxy, halogen, or amine groups, where at least one of the R groups is an alkoxy group and at least one of the R groups is an amine group.

[0036] In some preferred embodiments, R1, R2, and R3 comprise alkoxy functional groups and R4 comprises an amine group.

[0037] Examples of preferred alkoxysilanes include, but are not limited to, (3-aminopropyl)trimethoxysilane, 3-aminopropyltriethoxysilane, 4-aminobutyltriethoxysilane, m-aminophenyltrimethoxysilane, p-aminophenyltrimethoxysilane, 3-aminopropyltris(methoxyethoxyethoxy)silane, 11-aminoundecyltriethoxysilane, and 2-(4-pyridylethyl)triethoxysilane.

[0038] The alkoxysilane amine modified particles in the CMP slurries disclosed herein do not have an activator compound attached to them.

[0039] The surface treatment with the alkoxysilane amine compound occurs only on the surface of the particle. There is no shell formation surrounding the core silica particle.

[0040] The zeta potential of the particles in the slurry and DI water is 15 mV or greater, preferably 20 mV or greater, or more preferably 25 mV or greater.

[0041] The particle size as measured by dynamic light scattering is 10 to 300 nm, preferably 20 to 200 nm, or more preferably 30 to 100 nm.

[0042] In certain preferred embodiments, the abrasive is a cocoon-shaped highly agglomerated particle.

[0043] The slurry may have more than one type of abrasive and it may be advantageous to have different sizes for the different types of abrasive.

[0044] One type of abrasive can be a metal oxide, a metal oxide or semi-metal oxide, or a chemical mixture of metal oxides or semi-metal oxides.

[0045] Suitable metal oxide abrasives include, but are not limited to, alumina, ceria, germania, silica, spinel, titania, tungsten oxide or nitride, zirconia, or any of the above doped with one or more other minerals or elements, and any combination thereof. Metal oxide abrasives may be produced by any of a variety of techniques, including sol-gel, hydrothermal, hydrolytic, plasma, pyrogenic, aerogel, fuming and precipitation techniques, and any combination thereof.

[0046] Precipitated metal oxides and semi-metal oxides can be obtained by known processes by reaction with metal salts and acids or other precipitants. Pyrogenic metal oxide and / or semi-metal oxide particles can be obtained by hydrolysis of suitable vaporizable raw materials in an oxygen / hydrogen flame. An example is pyrogenic silicon dioxide from silicon tetrachloride. Pyrogenic oxides of aluminum oxide, titanium oxide, zirconium oxide, silicon dioxide, cerium oxide, germanium oxide and vanadium oxide as well as chemical and physical mixtures thereof are suitable.

[0047] The abrasive may be a mixed oxide, such as one consisting of the two molecular species SiO2 and Al2O3. Abrasives containing alumina-coated silica may also be useful.

[0048] In a preferred embodiment, the metal oxide abrasive is a precipitated or fumed abrasive, preferably a fumed abrasive. By way of example, the fumed metal oxide abrasive may be fumed silica or fumed alumina or fumed silica / alumina.

[0049] The abrasive particles can be purified using a suitable method, such as ion exchange, to remove metal impurities such as sodium, potassium, aluminum, iron, etc. Alternatively, high purity silica particles are used. In certain preferred embodiments, the total metal content in the silica particles is less than 100 ppm, or more preferably less than 10 ppm, or most preferably less than 1 ppm.

[0050] In general, the above abrasives can be used alone or in combination with each other. Also, two or more abrasive particles of different sizes can be combined to obtain superior performance.

[0051] In most embodiments of the present invention, the abrasive is selected from the group consisting of colloidal silica; fumed silica; alumina; titania; ceria; zirconia; surface modified particles selected from the group consisting of active agent-containing particles, composite particles, and lattice-doped inorganic oxide particles; and combinations thereof.

[0052] The concentration of the abrasive may range from 0.01% to 30% by weight, preferably from about 0.05% to about 10% by weight, and more preferably from about 0.1% to 2% by weight, where the weight percentage is based on the total weight of the composition.

[0053] Additives for reducing dishing or inhibiting tungsten corrosion The slurry formulation may include additives to reduce dishing of tungsten features or to reduce tungsten etching and corrosion during CMP.

[0054] Additives used in the slurry include, but are not limited to, sarcosinates, related carboxylic acid compounds, and hydrocarbon substituted sarcosinates; organic polymers and copolymers having molecules containing ethylene oxide repeat units, such as polyethylene oxide (PEO), as well as ethoxylated surfactants, nitrogen-containing heterocycles without nitrogen-hydrogen bonds, sulfides, oxazolidines or mixtures of functional groups in one compound, nitrogen-containing compounds having 3 or more carbon atoms forming alkylammonium ions, aminoalkyls having 3 or more carbon atoms, polymeric corrosion inhibitors containing at least one nitrogen-containing heterocycle or repeat group of tertiary or quaternary nitrogen atoms, such as cetyltrimethylammonium hydroxide, polycationic amine compounds, cyclodextrin compounds, polyethyleneimine compounds, glycolic acid, chitosan, sugar alcohols, polysaccharides, alginate compounds, phosphonium compounds, sulfonic acid polymers, amidine compounds, and polyacrylamides.

[0055] A preferred additive for reducing dishing and corrosion is a nitrogen-containing polymeric additive. The nitrogen-containing polymeric additive may include polymeric polyamines, such as chitosan, polyacrylamide, polyamines, polyethyleneimines, poly(N-vinyl-N-methylamines), polyaminostyrenes, polyvinylamines, polyvinyl amines (which may be homopolymers or copolymers).

[0056] In embodiments in which the nitrogen-containing polymer additive comprises a polyamine, the polyamine may comprise a diamine selected from 1,2-diaminoethane, 1,4-diaminobutane, 1,5-diaminopentane, 1,6-diaminohexane (hexamethylenediamine, HMDA), 1,12-diaminododecane, 1,4-diaminocyclohexane, 1,4-diaminobenzene, 1,5-diamino-2-methylpentane (2-methyl-pentamethylenediamine), 1,3-pentanediamine, and 1,8-diaminooctane. The nitrogen-containing reactant may comprise a primary polyamine polyether-polyamine; the polyether-polyamine may be a diamine or triamine. In one embodiment, the polyether-polyamine is a trifunctional primary amine having an average molecular weight of 440 known as Jeffamine T-403 Polyetheramine (Huntsman Corporation).

[0057] Generally speaking, for nitrogen-containing polymeric additives such as polyacrylamide, the molecular weight of the polymeric additive ranges from about 200 MW to about 500,000 MW, more preferably from about 500 MW to about 100,000 MW, even more preferably from about 1,000 MW to about 20,000 MW, and most preferably from about 5,000 MW to about 15,000 MW, where MW corresponds to the molecular weight expressed in grams per mole. Preferably, the polymeric additive does not substantially deposit on the surface of the microelectronic device.

[0058] In some embodiments, chitosan is the additive. Chitosan has the following structure: [ka] n is a number from 20 to 2,250 and preferably from 50 to 1,500; or from 200 to 1,000. Preferably, the chitosan used is 70% to 90% or 75% to 85% deacetylated.

[0059] In some embodiments, the compositions disclosed herein include at least one water soluble cationic polysaccharide as an additive for reducing dishing on tungsten metal.

[0060] The water-soluble cationic polysaccharides of the present invention can be prepared from readily available materials, derived from naturally occurring polysaccharides or those modified by etherification, quaternization with nitrogen-containing compounds, and alkylation with compounds, such as nitrogen-containing compounds, that contain hydrophobic groups.

[0061] Polysaccharide sources include naturally occurring, biosynthetic and derivatized carbohydrate polymers or mixtures thereof. Such materials include high molecular weight polymers composed of monosaccharide units linked by glycosidic bonds. These materials include whole starch and cellulose families; pectins; chitosan; chitin; seaweed products such as agar and carrageenan; alginates; natural gums such as guar, arabic and tragacanth; bio-derived gums such as xanthan, and the like. Preferred sources include celluloses conventionally used for the preparation of cellulose ethers, such as chemical cotton, cotton linters, wood pulp, alkali cellulose, and the like, and their ether derivatives. Such cellulose ethers include hydroxyethyl cellulose, hydroxypropyl cellulose, methyl cellulose, carboxymethyl cellulose, carboxyethyl cellulose, hydroxypropyl methyl cellulose, hydroxyethyl methyl cellulose, hydroxyethyl carboxymethyl cellulose, and the like. A particularly preferred polysaccharide source is hydroxyethyl cellulose. The polysaccharide source typically has a molecular weight corresponding to the number of polysaccharide repeating units, ranging from 50 to about 20,000. The molecular weight of the polysaccharides can be altered by controlled degradation procedures known in the art.

[0062] Etherified polysaccharides can be obtained commercially or produced from the aforementioned polysaccharide raw materials. Etherification involves reacting pendant hydroxyl groups on the polysaccharide backbone with an etherifying agent or mixtures thereof that contain functional groups reactive with such hydroxyl groups. Etherification can be carried out to increase the water solubility of the polysaccharide, for example, by ethoxylation. Typical etherifying agents include low alkylating agents, such as dimethyl sulfate, diethyl sulfate, methyl chloride, methyl bromide, ethyl chloride, ethyl bromide or n-propyl chloride; hydroxy alkylating agents, such as ethylene oxide, propylene oxide or glycidol; and carboxy alkylating agents, such as monochloroacetic acid, sodium chloroacetate or chloropropionic acid.

[0063] The polysaccharide raw material undergoes a quaternization reaction to impart quaternary nitrogen-containing substituents. Quaternization can be accomplished by reacting the polysaccharide with a quaternizing agent that is a quaternary ammonium salt (including mixtures thereof) to substitute the polysaccharide chains with quaternary nitrogen-containing groups. Exemplary quaternary ammonium salts that can be utilized include quaternary nitrogen-containing halides, halohydrins, and epoxides. The quaternary ammonium salts can contain hydrophobic groups. Exemplary ammonium salts include one or more of the following:

[0064] 3-Chloro-2-hydroxypropyldimethyldodecylammonium chloride;3-Chloro-2-hydroxypropyldimethyloctadecylammonium chloride;3-Chloro-2-hydroxypropyldimethyloctylammonium chloride;

[0065] 3-chloro-2-hydroxypropyltrimethylammonium chloride; 2-chloroethyltrimethylammonium chloride; 2,3-epoxypropyltrimethylammonium chloride, etc. Preferred quaternizing agents include 3-chloro-2-hydroxypropyltrimethylammonium chloride; 3-chloro-2-hydroxypropyldimethyldodecylammonium chloride; 3-chloro-2-hydroxypropyldimethyltetradecylammonium chloride;

[0066] 3-chloro-2-hydroxypropyldimethylhexadecyl ammonium chloride; and 3-chloro-2-hydroxypropyldimethyloctadecyl ammonium chloride.

[0067] Suitable water-soluble cationic polysaccharides can be made according to the disclosure of US Pat. No. 4,663,159, which is incorporated herein by reference.

[0068] In some embodiments, the cationic polysaccharides used herein as additives to prevent tungsten dishing are represented by the following general formula: [ka]

[0069] In formula I, R sacch is the residue of a polysaccharide repeat unit derived from the polysaccharide source described above. The polysaccharide repeat unit may contain more than three "R" substituents for those polysaccharides that contain more than three reactive hydroxyl groups per repeat unit, such as, for example, xanthan gum, which provides up to 11 hydroxyl groups per repeat unit available for etherification, quaternization, or alkylation. sacch is preferably a residue of an anhydroglucose repeating unit, in particular from cellulose.

[0070] The parameter Q in formula I varies depending on the particular polysaccharide utilized. For example, Q is --O-- when the particular polysaccharide contains anhydroglucose repeating units, such as in starch, cellulose, etc.

[0071] Similarly, Q is [ka] R4 is hydrogen and in chitosan [ka] Q is preferably —O—, i.e., an oxygen atom.

[0072] The number of polysaccharide repeating units defined by z in formula I is usually from about 50 to about 20,000, preferably from about 100 to about 6,000, and most preferably from about 250 to about 4,000. The corresponding molecular weights of the hydrophobically substituted cationic polysaccharides are usually in the range of several thousand to several million.

[0073] The R1, R2 and R3 substituents in formula I, when representing unreacted hydroxyl groups of the polysaccharide, are either hydrogen or those substituents provided by etherification, quaternization and / or alkylation. Each R1, R2 and R3 is individually represented by the substituent structural formula (II): [ka]

[0074] In formula II, A is an anion that includes a mixture of anions. Exemplary anions include inorganic anions such as chloride, bromide, iodide, sulfate, methyl sulfate, sulfonate, nitrate, phosphate, and the like; and organic anions such as acetate, and the like. Monovalent anions are preferred, particularly halides, and especially chloride. The anion is typically provided as the remainder of the quaternary ammonium salt used as the quaternizing agent, or by ion exchange techniques.

[0075] The alkylene substituent defined by a in formula II contains from 1 to about 3 carbon atoms, such that a is an integer having a value from 1 to about 3.

[0076] The degree of etherification by the oxyalkylene substituents defined by m and p in formula II each ranges from 0 to about 6 oxyalkylene groups, i.e., m is an integer from 0 to about 6 and p is an integer from 0 to about 6. An additional degree of etherification, defined by q in formula II, is achieved by increasing the alkylene group, i.e., C, such that q is 0 or 1, preferably 0. a H 2a It depends on whether

[0077] The overall degree of etherification is usually greater than 0, preferably from about 1.2 to about 4.5, and most preferably from about 1.8 to about 3.6.

[0078] The number of quaternary nitrogen atoms per substituent, defined by n in formula II, is from 0 to about 3, i.e., n is an integer from 0 to about 3. The degree of quaternization, characterized as above as CS, is greater than 0, more preferably less than 1, and most preferably from about 0.01 to about 0.6.

[0079] Each R5 and R7 defining an oxyalkylene substituent is independently an ethylene (to provide an oxyethylene), propylene (to provide an oxypropylene), or hydroxypropylene (to provide a hydroxy-substituted oxypropylene) unit. R5 and R7 are preferably ethylene or isopropylene, and most preferably ethylene.

[0080] The moiety linking the quaternary nitrogen to the polysaccharide molecule, defined as R6 in formula II, is a divalent or trivalent, branched or straight chain, saturated or unsaturated hydrocarbon having from 2 to about 4 carbon atoms, provided that there are at least 2 carbon atoms between the nitrogen atom and any oxygen atom, e.g., in the ether substituent or in the polysaccharide residue. R6 is preferably ethylene, a C3 hydrocarbon group, or —CH2CH=CHCH2—, most preferably [ka] It could be.

[0081] R in formula II is hydrogen, hydroxyl, R as defined below h , carboxyl or alkali metal or amine carboxylate, provided that when q is 0, R8 is hydrogen or R h R8 is preferably hydrogen or R h When R8 is hydrogen and m, n, p and q are all 0, the substituent structure provides an unsubstituted polysaccharide hydroxyl group.

[0082] In formula II, R 10 and R 11 Each nitrogen substituent defined by h The nitrogen substituent is preferably an alkyl, aryl, aralkyl, alkaryl, cycloalkyl, alkoxyalkyl, or alkoxyaryl. When an alkoxyalkyl or alkoxyaryl substituent is provided, at least two carbon atoms separate the substituent oxygen atom from the nitrogen atom. Nitrogen substituents that do not have hydrophobic properties include: lower alkyl having 1 to about 3 carbon atoms such as methyl or ethyl; aryl such as phenyl; aralkyl such as benzyl, and the like. Preferably, at least two of the nitrogen substituents in each repeat unit are methyl, with the remaining substituents being selected from the R of the nitrogen-containing repeat units in the polysaccharide molecule. h or R h and methyl.

[0083] In formula II, R hHydrophobic groups defined by contain long chain alkyl groups having at least 8 carbon atoms, preferably from about 10 to about 24 carbon atoms, and most preferably from about 10 or 12 to about 18 carbon atoms. Hydrophobic groups containing alkyl or aryl groups having fewer than 8 carbon atoms generally do not provide sufficient hydrophobic substitution in the quaternary nitrogen-containing polysaccharides to produce the excellent combination of properties exhibited by the hydrophobically substituted polysaccharides of the present invention.

[0084] In addition to being substantially water soluble, the polysaccharides disclosed herein contain hydrophobic groups containing 8 or more alkyl carbon atoms in an amount sufficient to provide enhanced viscosification, foaming, and preferably surface tension reduction of aqueous solutions containing the polysaccharides, as well as significant personal care benefits. Preferred polysaccharides of the present invention may provide significant personal care benefits, even at the expense of providing only marginal enhancements in viscosity, foaming, or surface tension properties.

[0085] R h , R9, R 10 Or R 11 directly attached to the quaternary nitrogen when present as R; attached to an ether substituent as R; and / or attached directly to the polysaccharide residue as R when m, n, p and q are all 0. Hydrophobic groups may be provided on the same or different repeat units within the polysaccharide molecule at any or all of these positions.

[0086] R h may also contain a linking moiety between the alkyl and ether oxygen atoms, depending on the functional groups contained in the alkylating agent used to link the alkyl group to the polysaccharide. For example, R h R can be: an alkyl group when an alkyl halide is the alkylating agent; an α-hydroxyalkyl group when an epoxide is the alkylating agent; a urethane alkyl group when an isocyanate is the alkylating agent; an acylalkyl group when the alkylating agent is a carboxylic acid or an acyl halide, etc. his preferably a long chain alkyl group attached directly to an oxygen atom or, most preferably, to a quaternary nitrogen atom.

[0087] The valency of the anion A, defined as v in formula II, is an integer, preferably one.

[0088] The absence or presence of ether oxygen in the quaternary nitrogen substituent is defined by y in formula II, i.e., y is 0 or 1, respectively, with the proviso that there are no further ether substitutions, i.e., when n is greater than 0 and y is 0, p and q are 0 and R8 is hydrogen. Preferably, y is 1.

[0089] The amount of these additives ranges from 0.0001% to about 2.0% by weight; preferably from about 0.001% to 1.0% by weight, and more preferably from 0.01% to about 0.5% by weight.

[0090] In one embodiment, the water soluble cationic polysaccharide is at least one represented by the following general formula: [ka] R sacch is the residue of a polysaccharide repeat unit derived from a polysaccharide source; Q is selected from the group consisting of: [ka] R4 is [ka] and, [ka] and hydrogen; Z is 50 to about 20,000; and each R1, R2, and R3 is independently represented by the following substituent structural formula: [ka] A is an anion; a is an integer from 1 to about 3; m is an integer from 0 to about 6; n is an integer from 0 to about 3, provided that the level of cationic substitution, CS, defined by the average number of moles of quaternary nitrogen atoms per mole of polysaccharide repeat unit, is greater than 0; p is an integer from 0 to about 6; q is 0 or 1; each R5 and R7 is independently ethylene, propylene, or hydroxypropylene; R6 is a divalent or trivalent, branched or straight chain, saturated or unsaturated hydrocarbon having from 2 to about 4 carbon atoms, provided that there are at least 2 carbon atoms between the nitrogen atom and any oxygen atom; R8 is hydrogen, hydroxyl, R h , carboxyl or alkali metal or amine carboxylate, provided that when q is 0, R8 is hydrogen or R h and; Each R9, R 10 and R 11 is individually Rh, alkyl, aryl, aralkyl, alkaryl, cycloalkyl, alkoxyaryl, or alkoxyalkyl having at least two carbon atoms separating the oxygen atom in the alkoxyaryl or alkoxyalkyl group from the nitrogen atom; R h is a hydrophobic group containing an alkyl group having at least 8 carbon atoms; v equals the valence of A; y is 0 or 1.

[0091] In some embodiments, when y is 0, then p and q are 0 and R8 is hydrogen.

[0092] In some embodiments, the additive is selected from the group consisting of at least one polyamine and at least one polyacrylamide. In some embodiments, the additive comprises chitosan and polyacrylamide. In other embodiments, the additive comprises chitosan and polyether-polyamine (Jeffamine T-403). In yet other embodiments, the additive comprises chitosan, polyacrylamide, and polyether-polyamine.

[0093] Oxidizing agent The CMP slurry of the present invention comprises 0.1 wt.% to about 10.0 wt.%; 0.5 wt.% to 5.0 wt.%; 1.0 wt.% to 3.0 wt.% of an oxidizer for chemical etching of a material. The oxidizer of the CMP slurry is in a fluid composition that contacts the substrate and aids in the chemical removal of the target material on the substrate surface. Thus, the oxidizer component is believed to enhance or increase the material removal rate of the composition. Preferably, the amount of oxidizer in the composition is sufficient to aid in the chemical removal process while being as low as possible to minimize similar or related issues such as handling, environmental, or cost.

[0094] Advantageously, in one embodiment of the present invention, the oxidizing agent is a component that generates free radicals when exposed to at least one activator, providing increased etching rates on at least selected structures. The free radicals described below oxidize most metals, making the surface more susceptible to oxidation from other oxidizing agents. However, the oxidizing agents are listed separately from the "Compound Producing Free Radicals" discussed below, because some oxidizing agents do not readily form free radicals when exposed to an activator, and in some embodiments, it is advantageous to have one or more oxidizing agents that provide matched etching or preferred etching rates on various combinations of metals that may be found on a substrate.

[0095] As is known in the art, some oxidizers are more suitable for certain components than others. In some embodiments of the invention, the selectivity of the CMP system for one metal as opposed to another metal is maximized, as is known in the art. However, in certain embodiments of the invention, the combination of oxidizers is selected to provide substantially similar CMP rates (as opposed to simple etch rates) for the combination of conductor and barrier.

[0096] In one embodiment, the oxidizing agent is an inorganic or organic percompound.

[0097] Per compounds are generally defined as compounds that contain an element in its highest state of oxidation, such as perchloric acid; or compounds that contain at least one peroxy group (-OO-), such as peracetic acid and perchromate.

[0098] Suitable per compounds containing at least one peroxy group include, but are not limited to, peracetic acid or its salts, percarbonic acid, and organic peroxides such as benzoyl peroxide, urea hydrogen peroxide, and / or di-t-butyl peroxide.

[0099] Suitable per compounds containing at least one peroxy group include peroxides. As used herein, the term "peroxide" encompasses ROO-R', where R and R' are each independently H, C1-C6 linear or branched alkyl, alkanol, carboxylic acid, ketone (for example), or amine, each of the above may be independently substituted with one or more benzyl groups (e.g., benzoyl peroxide), which may themselves be substituted with OH or C1-C5 alkyl, as well as salts and adducts thereof. Thus, the term includes common examples such as hydrogen peroxide, performic acid, peracetic acid, propaneperoxoic acid, substituted or unsubstituted butaneperoxoic acid, hydroperoxy-acetaldehyde, and the like. The term also encompasses common complexes of peroxides, such as urea peroxide.

[0100] Suitable per compounds containing at least one peroxy group include persulfates. As used herein, the term "persulfate" includes monopersulfate, dipersulfate, and their acids and salts and adducts. Included are, for example, peroxydisulfate, peroxymonosulfate and / or peroxymonosulfate, Caro's acid, including salts such as potassium peroxymonosulfate, but preferably non-metal salts such as ammonium peroxymonosulfate.

[0101] Suitable per compounds containing at least one peroxy group include the perphosphates defined above, including peroxydiphosphates.

[0102] Ozone is also a suitable oxidizing agent, either alone or in combination with one or more other suitable oxidizing agents.

[0103] Suitable per compounds that do not contain a peroxy group include, but are not limited to, periodic acid and / or any salts of periodates (hereinafter "periodates"), perchloric acid and / or any salts of perchlorates (hereinafter "perchlorates"), perbromic acid and / or any salts of perbromates (hereinafter "perbromates"), and perboric acid and / or any salts of perborates (hereinafter "perborates").

[0104] Other oxidizing agents are also suitable components of the compositions of the present invention. Iodate is a useful oxidizing agent.

[0105] Two or more oxidizers may be combined to provide synergistic performance benefits.

[0106] The oxidizer concentration can range from 0.01% to 30% by weight, although a more preferred amount of oxidizer is from about 0.5% to about 10% by weight, the weight percentages being of the composition.

[0107] In most embodiments of the present invention, the oxidizing agent is selected from the group consisting of peroxy compounds selected from the group consisting of hydrogen peroxide, urea peroxide, performic acid, peracetic acid, propane peracid, substituted or unsubstituted butane peracid, hydroperoxy-acetaldehyde, potassium periodate, ammonium peroxymonosulfate; and non-peroxy compounds selected from the group consisting of iron(III) nitrite, KClO4, KBrO4, KMnO4.

[0108] Activator An activator or catalyst is a substance that promotes the formation of free radicals by at least one free radical-producing compound present in the fluid. If the activator is a metal ion or a metal-containing compound, the activator is in a thin layer associated with the surface of a solid in contact with the fluid. If the activator is a non-metal-containing material, the activator can be dissolved in the fluid. The activator is preferably present in an amount sufficient to promote the desired effect.

[0109] For example, activators or catalysts described in U.S. Pat. Nos. 7,014,669, 6,362,104, 5,958,288, 8,241,375, 7,887,115, 6,930,054, U.S. Patent Application Publication Nos. 2014 / 315386, 2016 / 280962, and Korean Publication No. 10-2011-0036294, the disclosures of which are incorporated herein by reference, may be used in this amount.

[0110] The activator can be present in the slurry, or can be present on the polishing pad, or wherever the slurry containing the oxidizer comes into contact with the activator before passing between the pad and the wafer substrate.

[0111] The active agent may be present in one or more different forms. Examples of different forms of active agents include, but are not limited to, (i) soluble active agent compounds in a slurry, (ii) particles surface-modified with an active agent compound, (iii) particles having active agents contained in both the particle core and on the surface, and (iv) core-shell composite particles with surface-exposed active agents.

[0112] In one embodiment, the activator is any metal-containing compound known to be useful in the Fenton reaction as an activator, and the oxidant is a peroxide, particularly hydrogen peroxide. Transition metals such as copper, manganese, cobalt, and cerium, as well as the more traditional iron and copper, can catalyze this reaction.

[0113] In one important embodiment, the activator comprises a metal-containing compound having a metal other than a metal in Group 4(b), 5(b), or 6(b) of the Periodic Table of the Elements, hi one embodiment, compounds of metals in Group 1(b) or Group 8 are preferred metal-containing activators.

[0114] Metal-containing activator compounds can be used in forming soluble compounds in the slurry. Activator compounds suitable for the pH range of the present invention include, but are not limited to, ammonium iron(III) oxalate trihydrate, iron(III) citrate tribasic monohydrate, iron(III) acetylacetonate-ethylenediaminetetraacetic acid, sodium iron(III) salt hydrate. Soluble activators can also be metal compounds of Ag, Co, Cr, Cu, Fe, Mo, Mn, Nb, Ni, Os, Pd, Ru, Sn, Ti, V, and mixtures thereof with multiple oxidation states. In most embodiments of the present invention, activators include, but are not limited to, transition metals. Compounds of metals with strong chemical ligands, such as citrate, gluconate, oxalate, ethylenediaminetetraacetic acid, are generally stable at alkaline pH.

[0115] Some activated compounds, such as iron(III) nitrate, iron(III) sulfate, iron(III) citrate, and iron gluconate, are stable at acidic pH, such as pH below 4.

[0116] The amount of soluble activator compound in the slurry ranges from about 0.0001% to about 10% by weight; preferably 0.0005% to 2% by weight; more preferably 0.001% to 1% by weight; and most preferably 0.005% to 0.5% by weight.

[0117] In another important embodiment, the activator includes any transition metal-containing compound that can react with a compound that generates free radicals and is bound to a solid. That is, the activator of the present invention is not dissolved in a fluid. The activator can be bound to a particle. The particle can be an abrasive, or it can be a carrier for the activator. In some preferred embodiments, the activator can be chemically or physically adsorbed on the surface of the abrasive as a molecular species, small particle, or as a monolayer or partial layer. In some other embodiments, the abrasive can be a co-formed abrasive, where the activator is mixed uniformly with another oxide to form a solid particle containing an intimate mixture of the activator supported on the metal oxide.

[0118] Iron bound to an abrasive is particularly useful and is the most preferred activator. Iron bound to silica is the most preferred system. Silica, with its many OH groups, can multiple bond with iron, keeping the iron tightly bound to the silica by many covalent and / or ionic type bonds. However, the multiple binding of iron onto absorbed, adsorbed, or coated silica allows for easy conversion between oxidation states, without the iron having a tendency to separate from the silica surface. Surprisingly, iron bound to silica can be used at high pH values, e.g., pH 5 to pH 7, and in some cases up to pH 12.

[0119] Iron can be combined with the abrasive in the form of a salt, such as a ferric salt, a ferrous salt, in some forms as ferric oxide, and in some forms as metallic metal. Generally, the metallic metal is converted to the ferric or ferrous form in the presence of an oxidizing agent. An added advantage of iron is that it is environmentally friendly and does not pose significant disposal problems.

[0120] Systems having slurries with iron activators, i.e., iron coated on the solid particles contained within the slurry, exhibit excellent free radical activity when the amount of activator iron is about 2-500 ppm total activator iron, preferably 3-100 ppm total activator iron, and for low iron embodiments, about 4-20 ppm total activator iron. Iron that is not in contact with the fluid, including, for example, iron within the particle matrix that is not capable of generating free radicals that can escape the particle structure, is not included in the term activator iron. Iron that is not capable of activating the formation of free radicals is not included in activated iron, for example, because it is incorporated within a matrix where changes between oxidation states are not encouraged. Finally, iron that is chelated or otherwise unavailable for reaction with compounds that generate free radicals is not included as activated iron. An exemplary slurry has about 10 ppm to about 300 ppm total activator iron, the majority of which is absorbed, adsorbed, or coated on the abrasive.

[0121] Particles containing an activator compound may be used in the CMP slurry in a concentration range of 0.01% to 2% by weight, or preferably 0.05% to 1% by weight, or most preferably 0.07% to 0.5% by weight.

[0122] The activator may be a non-metal-containing compound. Iodine is useful, for example, with hydrogen peroxide to form free radicals. Iodine may be present in an amount sufficient to generate the desired free radical activity. In some embodiments, iodine may be present in an amount ranging from about 1 ppm to about 5,000 ppm, preferably from about 10 ppm to about 1,000 ppm. Non-metal activators are often synergistically combined with metal-containing activators.

[0123] The activator may also be a light-activated activator such as titanium dioxide (and light used as the activator). The light-activated materials of U.S. Patent No. 6,362,104 may be used in this amount, the disclosure of which is incorporated by reference.

[0124] Water-miscible organic solvent (optional) The polishing composition of the present invention optionally contains one or more water-miscible organic solvents. Examples of water-miscible organic solvents that can be used are ethylene glycol, propylene glycol, 1,4-butanediol, tripropylene glycol methyl ether, propylene glycol propyl ether, diethylene glycol n-butyl ether (e.g., commercially available under the trade name Dowanol DB), hexyloxypropylamine, poly(oxyethylene)diamine, dimethylsulfoxide, tetrahydrofurfuryl alcohol, glycerol, alcohol, sulfoxide, or mixtures thereof. Preferred solvents are alcohols, diols, or mixtures thereof. Most preferred solvents are diols, such as propylene glycol.

[0125] For most applications, the amount of water-miscible organic solvent, if present, will comprise from about 5 to about 75% by weight of the composition. Preferably, the solvent comprises from 5 to about 50% by weight of the composition, and most preferably from about 5 to about 30% by weight.

[0126] In some embodiments, the compositions of the present invention are free or substantially free of any or all of the above water-miscible organic solvents added to the composition, and are free or substantially free of all water-miscible organic solvents.

[0127] pH adjuster The pH of the composition is desirably on the order of about pH1 to about pH14, and preferably about pH1 to about pH7, and more preferably about pH2 to about pH5.

[0128] An acidic or basic pH adjuster, such as a suitable acid, base, amine, or any combination thereof, can be used to adjust the CMP polishing composition to an optimized pH value.

[0129] pH adjusters include, but are not limited to, acidic pH adjusters, such as nitric acid, hydrochloric acid, sulfuric acid, phosphoric acid, other inorganic or organic acids, mixtures thereof, and other chemical reagents that can be used to adjust the pH in a more acidic direction.

[0130] pH adjusters also include basic pH adjusters such as sodium hydride, potassium hydroxide, ammonium hydroxide, tetraalkylammonium hydroxide, organic quaternary ammonium hydroxide compounds, organic amines, and other chemical reagents that can be used to adjust the pH in a more alkaline direction.

[0131] Preferably, the pH adjusters used in the composition do not contain metal ions so that undesirable metal components are not introduced into the composition.

[0132] The amount of pH adjuster in the slurry ranges from about 0.0001% by weight to about 2.0% by weight.

[0133] Biocides In certain embodiments, the CMP composition further comprises a biocide. The use of a biocide in an encapsulated CMP polishing composition reduces or eliminates bacteria and other microorganisms, especially when the pH value of the CMP polishing composition is close to or near neutral pH conditions.

[0134] The biocide or biological growth inhibitor is selected from the group consisting of tetramethylammonium chloride, tetraethylammonium chloride, tetrapropylammonium chloride, alkylbenzyldimethylammonium chloride, and alkylbenzyldimethylammonium hydroxide, where the alkyl chain ranges from 1 to about 20 carbon atoms, sodium chlorite, sodium hypochlorite, and combinations thereof.

[0135] The biocide ranges from about 0.0001% to about 0.03% by weight.

[0136] Accelerator As noted above, metals with multiple oxidation states dissolved in the fluid contacting the substrate can act as oxidants, however, the most preferred embodiments of the invention are substantially free of metals with multiple oxidation states.

[0137] In some embodiments, compounds of Al, Ag, Ce, Co, Cr, Cu, Fe, Mo, Mn, Nb, Nd, Ni, Os, Pd, Pt, Rh, Ru, Sc, Sm, Ta, Ti, V, or W dissolved in small amounts in the solution are useful. These are believed to promote the action of the oxidizer, as described in U.S. Pat. No. 5,958,288, the disclosure of which is incorporated herein by reference. Metal ions in solution are believed to act as oxidizers with some affinity for substrates, especially metal substrates. There is some synergy between the two species when they can be oxidized by other oxidizers in the fluid. However, in most cases, the accelerator is believed not to promote the action of free radicals. Compounds that form accelerators when exposed to the catalyst or substrate, such as those compounds described in U.S. Pat. No. 5,863,838, the disclosure of which is incorporated herein by reference, are also useful.

[0138] In some embodiments of the present invention, the fluid composition in contact with the substrate has a small amount of a metal ion oxidizer, referred to herein as an accelerator. Soluble compounds or salts of copper, aluminum, cerium, and iron are used as oxidizers or accelerators in the CMP solution. When used, the preferred metal-containing oxidizer accelerators are soluble cerium or aluminum salts.

[0139] The amount of accelerator in the slurry ranges from about 0.0001% to about 1.0% by weight; preferably from 0.0005% to 0.5% by weight, and more preferably from 0.0025% to 0.1% by weight.

[0140] Chelating Agents If (dissolved) metal-containing embodiments are not desired, the fluid may have a chelating agent. The chelating agent can essentially capture and isolate metals with multiple oxidation states that are present in dissolved form in the fluid. When the dissolved metals are in chelated form, it essentially isolates them from the substrate, impairing their efficiency as promoters, but preventing metal ion contamination. However, this can extend the pot life of the oxidizer slurry, and the chelating agent at low concentrations does not effectively impair the efficiency of the free radicals.

[0141] Therefore, only small amounts of chelating agents should be used. Chelating agents generally contain organic acid moieties that can act as free radical scavengers. This can adversely affect the performance of the system.

[0142] In most embodiments of the present invention, chelating agents include, but are not limited to, organic carboxylic acids, organic sulfonic acids, and organic phosphoric acids.

[0143] Generally, less than 3% by weight of chelating agent is preferred, preferably less than 1% by weight, for example less than 0.5% by weight.

[0144] Stabilizers The composition may also include one or more of various optional additives. Suitable optional additives include stabilizers. These optional additives are generally used to facilitate or promote the stabilization of the composition against settling, agglomeration (including particle precipitation, strong or weak agglomeration, etc.), and decomposition. Stabilizers can be used to extend the pot life of oxidizing agents, including compounds that generate free radicals, by isolating the activator material, quenching the free radicals, or otherwise stabilizing the compounds that form free radicals.

[0145] Several materials are useful for stabilizing hydrogen peroxide. One exception to metal contamination is the presence of selected stabilizing metals, such as tin. In some embodiments of the invention, tin can be present in small amounts, typically less than about 25 ppm, e.g., about 3 to about 20 ppm. Similarly, zinc is also commonly used as a stabilizing agent. In some embodiments of the invention, zinc can be present in small amounts, typically less than about 20 ppm, e.g., about 1 to about 20 ppm. In another preferred embodiment, the fluid composition contacting the substrate has less than 500 ppm, e.g., less than 100 ppm, of dissolved metals with multiple oxidation states, excluding tin and zinc. In the most preferred commercial embodiment of the invention, the fluid composition contacting the substrate has less than 9 ppm of dissolved metals with multiple oxidation states, excluding tin and zinc, e.g., less than 2 ppm of dissolved metals with multiple oxidation states. In some preferred embodiments of the invention, the fluid composition contacting the substrate has less than 50 ppm, preferably less than 20 ppm, and more preferably less than 10 ppm of dissolved total metals, excluding tin and zinc.

[0146] Since metals in solution are generally not recommended, these non-metal-containing oxidizers are typically preferably present in a salt form, such as a persulfate, an acid form, and / or an ammonium salt form, such as ammonium persulfate.

[0147] Other stabilizers include free radical scavengers. As discussed, these impair the usefulness of the free radicals that are generated. Therefore, when present, they are preferably present in small amounts. Most antioxidants, i.e., vitamin B, vitamin C, citric acid, etc., are free radical quenchers. While most organic acids are free radical quenchers, three that are effective and have other beneficial stabilizing properties are phosphonic acid, the binding agent oxalic acid, and the non-radical sequestering agent gallic acid.

[0148] Additionally, carbonates and phosphates are believed to bind onto the activator and prevent fluid access. Carbonates are particularly useful because they can be used to stabilize the slurry, but small amounts of acid can quickly remove the stabilizing ions. A useful stabilizing agent for absorbed activators can be a film former that forms a film on the silica particles.

[0149] Suitable stabilizers include organic acids such as adipic acid, phthalic acid, citric acid, malonic acid, orthophthalic acid; and phosphoric acid; substituted or unsubstituted phosphonic acids, i.e., phosphonate compounds; nitriles; and other ligands that bind to the activator material and thus reduce the reaction of decomposing the oxidizer, as well as any combination of the aforementioned agents. As used herein, acid stabilizer refers to both the acid stabilizer and its conjugate base. That is, various acid stabilizers can also be used in their conjugated form. By way of example, herein, adipic acid stabilizers include adipic acid and / or its conjugate base, and carboxylic acid stabilizers include carboxylic acids and / or their conjugate bases, carboxylates, etc. for the above acid stabilizers. Suitable stabilizers, used alone or in combination with one or more other stabilizers, reduce the rate at which an oxidizer, such as hydrogen peroxide, decomposes when mixed into a CMP slurry.

[0150] On the other hand, the presence of a stabilizer in the composition may impair the effectiveness of the activator. The amount should be adjusted to meet the required stability with the least adverse effect on the effectiveness of the CMP system. In general, any of these optional additives should be present in an amount sufficient to substantially stabilize the composition. The amount required will vary depending on the particular additive selected and the particular configuration of the CMP composition, such as the surface properties of the polishing components. If too little additive is used, the additive will have little or no effect on the stability of the composition. On the other hand, if too much additive is used, the additive may contribute to the formation of undesirable foaming and / or agglomerates in the composition.

[0151] Generally, suitable amounts of these optional additives range from about 0.0001% to about 2.0% by weight of the composition, preferably from about 0.0005 to 1.0% by weight, or more preferably from 0.001 to 0.5% by weight. These optional additives may be added directly to the composition or may be applied to the surface of the abrasive component of the composition.

[0152] In certain embodiments including an activator compound attached to a solid surface, a stabilizer compound may not be required to prevent decomposition of the oxidizer once added to the slurry.

[0153] The preferred stabilizer is malonic acid.

[0154] Surfactants If a surfactant is added to the CMP slurry, then the surfactant may be an anionic, cationic, nonionic, zwitterionic or amphoteric surfactant, or a combination of two or more surfactants may be employed.

[0155] A variety of anionic and cationic surfactants with molecular weights ranging from less than 1000 to more than 30,000 are contemplated as dispersants, including lauryl sulfate, alkyl polyphosphates, dodecylbenzene sulfonates, diisopropyl naphthalene sulfonates, dioctyl sulfosuccinates, ethoxylated and sulfated lauryl alcohol, and ethoxylated and sulfated alkyl phenols.

[0156] Various cationic surfactants include polyethyleneimines, ethoxylated fatty amines and stearylbenzyl dimethyl ammonium chloride or nitrate. Additional dispersing agents contemplated in the present invention include polyethylene glycols, lecithins, polyvinylpyrrolidones, polyoxyethylenes, isooctylphenyl ethers, polyoxyethylene nonylphenyl ethers, amine salts of alkylarylsulfonic acids, polyacrylates and related salts, polymethacrylates.

[0157] In general, the surfactant that can be used in the CMP slurry should be sufficient to achieve effective stabilization of the slurry, and typically varies depending on the specific surfactant selected and the surface properties of the metal oxide abrasive.For example, if the selected surfactant is used in an insufficient amount, it will have little or no effect on CMP slurry stabilization.On the other hand, too much surfactant in the CMP slurry may cause undesirable foaming and / or agglomeration in the slurry.

[0158] It has also been found that the addition of a surfactant can be useful in reducing the within-wafer non-uniformity (WIWNU) of the wafer, thereby improving the surface of the wafer and reducing wafer defects.

[0159] There are many suitable surfactant additives for the composition, but preferred surfactant additives include sodium dodecyl sulfate, sodium lauryl sulfate, ammonium dodecyl sulfate, and any combination thereof. Suitable commercially available surfactants include TRITON DF 16 (trademark) manufactured by Union Carbide and SURFYNOL (trademark) manufactured by Air Products and Chemicals.

[0160] The surfactant is generally present in the slurries of the present invention in an amount ranging from about 0.001 to about 0.2% by weight, preferably from about 0.001 to about 0.1% by weight.

[0161] Additionally, the additives may be added directly to the slurry or may be treated onto the surface of the metal oxide abrasive using known techniques, in either case the amount of additive being adjusted to achieve the desired concentration in the polishing slurry.

[0162] The components of the CMP slurry of the present invention may be mixed together as a single component slurry or may be provided in two or more components that are mixed at the point of use. It may be preferred to add an oxidizer at the point of use. In certain preferred embodiments, the slurry may be provided in a concentrated form so that it can be diluted with water and the oxidizer added before use. The slurry may be concentrated so that the water that can be added at the point of use is preferably two times the volume of the slurry, or more preferably more than three times the volume of the slurry, or most preferably more than five times the volume of the slurry. EXAMPLES

[0163] General experimental procedure Parameters Å: Angstrom (s) - unit of length

[0164] BP: Back pressure, unit psi

[0165] CMP: Chemical mechanical planarization = chemical mechanical polishing

[0166] DF: Downforce: pressure applied during CMP, in psi

[0167] min:minutes

[0168] ml: milliliter

[0169] mV: millivolt

[0170] psi: pounds per square inch

[0171] PS: Polishing tool platen rotation speed in rpm (revolutions per minute)

[0172] SF: polishing composition flow, ml / min

[0173] TEOS: Silicon oxide films by chemical vapor deposition (CVD) using tetraethyl orthosilicate as precursor

[0174] Removal rate (RR) = (film thickness before polishing - film thickness after polishing) / polishing time.

[0175] All component concentrations are in weight percent unless otherwise indicated.

[0176] In the examples presented below, CMP experiments were performed using the procedures and experimental conditions given below.

[0177] The CMP tool used in the examples is Mirra, manufactured by Applied Materials, USA. IC1010 polishing pads supplied by Dow Chemicals were used for the CMP process.

[0178] Silicon wafers of 200 mm diameter (obtained from SKW Associates, Inc 2920 Scott Blvd. Santa Clara, CA 95054) coated with tungsten or TEOS films or with tungsten-containing patterned structures were used. The polishing time for the blanket film was 1 minute. Tungsten removal rate was measured using a sheet resistance measurement technique. TEOS removal was measured using an optical technique. The patterned wafers were polished with a time based eddy current technique on an Ebara polisher. The polishing time for the patterned wafer was 15 seconds past the endpoint identified by the eddy current endpoint technique. The patterned wafers were analyzed using a KLA Tencor P15 Profiler (large feature size) or an AFM tool (small feature size).

[0179] Polishing was performed using a down force of 3 psi, a table speed of 80 RPM, a carrier speed of 81 RPM and a slurry flow rate of 100 ml / min.

[0180] Example 1 Base Formulation 1 contained 0.01 wt % iron(III) nitrate, 0.08 wt % malonic acid (a stabilizer), 2.5 wt % hydrogen peroxide, 0.1 wt % glycine, and 0.0005 wt % cetyltrimethylammonium hydroxide in water adjusted to a pH of 2.3.

[0181] Different abrasive particles were added to the base formulation to make the abrasive slurries. All particles used in this study were obtained from Fuso Chemical Co., Ltd. (2-2-5 Nihonbashi Honcho, Chuo-ku, Tokyo 103-00, Japan).

[0182] Fuso PL-3 is a cocoon-shaped silica particle with a particle size of about 70 nm. Fuso PL-3C is a cocoon-shaped silica particle with a particle size of about 70 nm that is surface-modified with an aminopropyltrialkoxysilane compound. Fuso PL-3L is a spherical silica particle with a particle size of about 70 nm. [Table 1]

[0183] Formulation 7 had the same amounts of chemicals as Formulation 6, except that it had 1.0% hydrogen peroxide by weight.

[0184] Table 1 and Figure 1 summarize the tungsten and TEOS removal rates for slurries formulated with different particles.

[0185] The data in Table 1 show that the use of alkoxysilane amine modified abrasive particles increased the removal rate of tungsten and concomitantly decreased the removal rate of TEOS, resulting in a significant increase in the removal selectivity of the tungsten vs. TEOS blanket from 3 or 11 to over 44.

[0186] Polishing rates for tungsten blanket films at a down force of 3.0 psi and a table speed of 80 RPM have been shown to be greater than 2500 Å / min, greater than 3000 Å / min, greater than 4000 Å / min, or greater than 4500 Å / min.

[0187] Example 2 For these formulations, dishing and erosion data for different patterned structures with different line features (2 μm×2 μm, 5 μm×5 μm, 10 μm×10 μm, 100 μm×100 μm, 7 μm×3 μm, 9 μm×1 μm) at 20% overpolish are summarized in Table 2 and Figure 2, and Table 3 and Figure 3, respectively.

[0188] Table 2. Dishing (Angstroms) [Table 2]

[0189] Table 3 Erosion (Angstroms) [Table 3]

[0190] The dishing and erosion data shown in Tables 2 and 3 show that by using alkoxysilane amine modified abrasive particles, the removal selectivity of tungsten vs. TEOS blanket was increased without affecting dishing and erosion of the array structures.

[0191] The dishing and erosion of some array structures was improved.

[0192] Erosion of a 9×1 micron array (9 micron wide tungsten lines separated by 1 micron wide dielectric lines) measured on patterned wafers was less than 1000 Å, less than 500 Å, or less than 300 Å when the wafer was polished for an additional 15 seconds after the patterned wafer polishing endpoint detected by using an appropriate method such as eddy current measurement or optical endpoint detection.

[0193] Example 3 The following formulations were made for comparison: [Table 4]

[0194] The ingredients were mixed in DI water and stirred. The table represents the formulation as-used.

[0195] Example 4: Effect of chitosan on erosion The following table summarizes the formulations that were evaluated for the erosion inhibition effect of chitosan on TEOS dielectrics: [Table 5]

[0196] 4-6 show the erosion inhibition results for varying amounts of chitosan on different sized features in a TEOS dielectric layer.

[0197] Example 5 Formulations 8 and 9 above were tested against each other for their effects on tungsten dishing and dielectric erosion.

[0198] The table below shows that chitosan and polyacrylamide when used together show improved dishing and erosion compared to a similar formulation in which the polyacrylamide was replaced with Jeffamine® T-403.

[0199] [Table 6] [Table 7]

[0200] Example 6: Effect on tungsten dishing The following formulations were prepared for evaluation of tungsten dishing: [Table 8]

[0201] The results are shown in Figures 7 and 8, where it is shown that a synergistic effect in minimizing tungsten dishing is observed between chitosan and polyacrylamide and different feature sizes.

[0202] Example 7 The base formulation, as a reference for Example 7, contained 0.02 wt. % iron (III) nitrate, 0.08 wt. % malonic acid (as a stabilizer), 3.0 wt. % hydrogen peroxide, 0.1 wt. % glycine, 0.3 wt. % Fuso PL-2C high purity colloidal silica particles as an abrasive, and 0.00056 wt. % Neolone M-10 as a biocide in water adjusted to a pH of 2.3.

[0203] The experimental formulations in Example 7 were prepared by adding chitosan having a molecular weight of 10-50 KDa or chitosan having a molecular weight of 80-200 KDa as an additive to the base formulation at a concentration of 30 ppm or 60 ppm, respectively. The pH was adjusted to 2.3 for all test formulations.

[0204] The effect of chitosan molecular weight and concentration on the W removal rate and TEOS film removal rate is listed in Table 4.

[0205] Table 4. Effect of chitosan MW and concentration on W RR and TEOS RR [Table 9]

[0206] As a result, as shown in Table 4, when two different molecular weight chitosans were used as additives at a concentration of 30 ppm, the W film removal rate increased by about 9%, while the TEOS film removal rate changed minimally.

[0207] Example 8 The same formulation described in Example 7 was used in Example 8. The effect of chitosan molecular weight and concentration on W interconnect dishing was summarized in Table 5.

[0208] Table 5. Effect of chitosan MW and concentration on W wiring dishing [Table 10]

[0209] As the results shown in Table 5, W wire dishing was improved using appropriate molecular weight and concentration of chitosan.

[0210] Example 9 The base formulation for Example 9 as a reference is the same formulation as described in Example 7.

[0211] The effect of chitosan molecular weight and concentration on erosion is listed in Table 6.

[0212] Table 6. Effect of chitosan MW and concentration on erosion [Table 11]

[0213] As the results are shown in Table 6, erosion was improved for all formulations except for the higher concentration of chitosan in the 50x50mm.

[0214] The foregoing examples and description of the embodiments should be construed as illustrative, rather than limiting, of the invention as defined by the claims. As will be readily appreciated, numerous variations and combinations of the features described above can be utilized without departing from the invention as set forth in the claims. Such variations are intended to be included within the scope of the following claims.

Claims

1. water; abrasive particles comprising 0.05% to 10.0% or 0.01% to 2.0% silica by weight; 0.0005% to 2% or 0.001% to 1% by weight of a soluble active compound; 0.5% to about 10.0% or 0.5% to 5.0% by weight of an oxidizing agent; At least one nitrogen-containing polymer additive selected from the group consisting of chitosan, polyacrylamide, polyamine, polyethyleneimine, poly(N-vinyl-N-methylamine), polyaminostyrene, polyvinylamine, and (polyvinyl)amine; and Optionally, Corrosion inhibitors; Stabilizers; pH adjuster; Water-miscible organic solvents; Surfactants; and Biocides or biological growth inhibitors; wherein the polishing composition has a pH of 2 to 14 or 1 to 7.

2. 10. The polishing composition of claim 1, wherein the abrasive particles are silica particles having a surface treated with an alkoxysilane amine and have a zeta potential of 15 mV or greater, or 25 mV or greater.

3. 2. The polishing composition of claim 1, wherein the abrasive particles have a particle size of 20 to 200 nm.

4. The at least one nitrogen-containing polymeric additive comprises chitosan, the chitosan being represented by the structure: 【Chemistry 1】 2. The polishing composition of claim 1, wherein n is a number between 20 and 2,250 or between 200 and 1,000; and the chitosan used is 70% to 90% or 75% to 85% deacetylated.

5. The at least one nitrogen-containing polymeric additive is Chitosan represented by the following structure: 【Chemistry 2】 2. The polishing composition of claim 1, wherein n is a number from 20 to 2,250 or from 200 to 1,000; the chitosan used is 70% to 90% or 75% to 85% deacetylated; polyacrylamide; and polyamine.

6. The polyamine is a polyether-polyamine having the structure 【Chemistry 4】 The polishing composition of claim 5 , wherein (x+y+z)=5 or 6.

7. 2. The polishing composition of claim 1, wherein the abrasive particles are silica particles having a surface treated with an alkoxysilane amine and have a zeta potential of 15 mV or greater, or 25 mV or greater; and the alkoxysilane amine is selected from the group consisting of (3-aminopropyl)trimethoxysilane, 3-aminopropyltriethoxysilane, 4-aminobutyltriethoxysilane, m-aminophenyltrimethoxysilane, p-aminophenyltrimethoxysilane, 3-aminopropyltris(methoxyethoxyethoxy)silane, 11-aminoundecyltriethoxysilane, 2-(4-pyridylethyl)triethoxysilane, and combinations thereof.

8. 2. The polishing composition of claim 1, wherein the pH is from 2 to 5.

9. the soluble activator compound is selected from the group consisting of ammonium iron(III) oxalate trihydrate, iron(III) citrate tribasic monohydrate, iron(III) acetylacetonate and ethylenediaminetetraacetic acid, iron(III) sodium salt hydrate; the activator compound coated on a solid particle is iron coated on a solid particle; and The oxidizing agent is a peroxy compound selected from the group consisting of hydrogen peroxide, urea peroxide, performic acid, peracetic acid, propaneperoxoic acid, substituted or unsubstituted butaneperoxoic acid, hydroperoxy-acetaldehyde, potassium periodate, and ammonium peroxymonosulfate; and iron(III) nitrite, KClO 4 , KBrO 4 , KMnO 4 2. The polishing composition of claim 1, wherein the compound is selected from the group consisting of non-peroxy compounds selected from the group consisting of:

10. 2. The polishing composition of claim 1, wherein the soluble activator is selected from the group consisting of iron (III) nitrate, iron (III) sulfate, iron (III) citrate, iron gluconate, and combinations thereof, and the composition has a pH of less than 4.

11. The polishing composition comprises: the water-miscible organic solvent being an alcohol; the corrosion inhibitor selected from the group consisting of glycine, lysine, alanine, proline, serine, arginine, and combinations thereof; said stabilizing agent being selected from the group consisting of organic acids and their conjugate bases selected from the group consisting of adipic acid, phthalic acid, citric acid, malonic acid, orthophthalic acid; phosphoric acid; substituted or unsubstituted phosphonic acids, nitriles; and combinations thereof; (a) for lowering the pH of the polishing composition, a pH adjuster selected from the group consisting of nitric acid, sulfuric acid, tartaric acid, succinic acid, citric acid, malic acid, malonic acid, various fatty acids, various polycarboxylic acids, and combinations thereof; and (b) for raising the pH of the polishing composition, a pH adjuster selected from the group consisting of potassium hydroxide, sodium hydroxide, ammonia, tetraethylammonium hydroxide, ethylenediamine, piperazine, polyethyleneimine, modified polyethyleneimine, and combinations thereof; and (a) a nonionic surface wetting agent; (b) an anionic surface wetting agent; (c) a cationic surface wetting agent; (d) an amphoteric surface wetting agent; and combinations thereof; the amount of said surfactant ranges from about 0.0001% to about 1.0% by weight, and preferably from about 0.010% to about 0.1% by weight. The polishing composition of claim 1 , comprising at least one selected from the group consisting of:

12. water; abrasive particles comprising 0.05% to 10.0% or 0.01% to 0.5% silica by weight; 0.0005% to 2% or 0.005% to 0.5% by weight of a soluble active compound; 0.5% to about 10.0% or 1.0% to 3.0% by weight of an oxidizing agent; At least one water-soluble cationic polysaccharide represented by the general formula: Includes: 【Chemistry 5】 R sacch is the residue of a polysaccharide repeat unit derived from a polysaccharide source; Q is selected from the group consisting of: 【Chemistry 6】 R 4 teeth, 【Chemistry 7】 and, 【Chemistry 8】 and hydrogen; Z is 50 to about 20,000; and each R1, R2, and R3 is independently represented by the following substituent structure: 【Chemistry 9】 A is an anion; a is an integer from 1 to about 3; m is an integer from 0 to about 6; n is an integer from 0 to about 3, provided that the level of cationic substitution, CS, defined by the average number of moles of quaternary nitrogen atoms per mole of polysaccharide repeat unit, is greater than 0; p is an integer from 0 to about 6; q is 0 or 1; Each R 5 and R 7 is individually ethylene, propylene, or hydroxypropylene; R 6 is a divalent or trivalent, branched or straight chain, saturated or unsaturated hydrocarbon having from 2 to about 4 carbon atoms, provided that there are at least 2 carbon atoms between the nitrogen atom and any oxygen atom; R 8 is hydrogen, hydroxyl, R h , carboxyl or alkali metal or amine carboxylate, provided that when q is 0, R 8 is hydrogen or R h and Each R 9 , R 10 and R 11 is individually Rh, alkyl, aryl, aralkyl, alkaryl, cycloalkyl, alkoxyaryl, or alkoxyalkyl having at least two carbon atoms separating the oxygen atom in the alkoxyaryl or alkoxyalkyl group from the nitrogen atom; R h is a hydrophobic group containing an alkyl group having at least 8 carbon atoms; v is equal to the valence of A; and A polishing composition, wherein y is 0 or 1, and the polishing composition has a pH of 2-14 or 1-7.

13. The composition further includes a polyether-polyamine or a polyacrylamide, the polyether-polyamine having the structure: 【Chemistry 10】 The polishing composition of claim 12 , wherein (x+y+z)=5 or 6.

14. 1. A polishing method for chemical mechanical planarization of a semiconductor device including at least one surface containing tungsten, the method comprising: a) contacting at least one tungsten-containing surface with a polishing pad; b) delivering the polishing composition of claim 1 or 12 to at least one tungsten-containing surface; and c) polishing at least one tungsten-containing surface with the polishing composition; wherein the polishing rate of tungsten at a down force of 3 psi is greater than 1000 Å / min.

15. 15. The polishing method of claim 14, wherein the semiconductor device further comprises a dielectric layer selected from the group consisting of TEOS; a porous or non-porous low-K film comprising silicon, carbon, oxygen and hydrogen; a porous low-K material with a capping layer of a non-porous material; and the removal rate selectivity between tungsten and the dielectric layer is greater than 1.

16. 16. The polishing method of claim 15, wherein the dielectric layer is TEOS; the polishing rate of TEOS at a down force of 3 psi is less than 150 Å / min, or less than 50 Å / min; and the removal rate selectivity between tungsten and TEOS is greater than 25, or greater than 90.

17. 1. A polishing system for chemical mechanical planarization of a semiconductor device including at least one surface containing tungsten; a) at least one surface containing said tungsten; b) a polishing pad; and c) The polishing composition according to claim 1 or 12. wherein the at least one tungsten-containing surface is in contact with the polishing pad and the polishing composition.

18. 20. The polishing system of claim 17, wherein the semiconductor device further comprises a dielectric layer selected from the group consisting of TEOS; a porous or non-porous low-K film comprising silicon, carbon, oxygen and hydrogen; a porous low-K material having a capping layer of a non-porous material; and the removal rate selectivity between tungsten and the dielectric layer is greater than 1.

19. 20. The polishing system of claim 18, wherein the dielectric layer is TEOS; the polishing rate of TEOS at a downforce of 3 psi is less than 150 Å / min, or less than 50 Å / min; and the removal rate selectivity between tungsten and TEOS is greater than 25, or greater than 90.

20. The polishing method according to claim 14, wherein the polishing composition has a pH of 2 to 5.